Pengaruh Pelatihan Sumber Daya Insani Terhadap Kinerja Karyawan BMT-UGT Sidogiri di Surabaya dan Sidoarjo - Rahmayani, Azizah Nur; Prasetya, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purposes of employees training are to improve, develop, and enhance theirÂ skills. In an organization, the scoring of employeesâ performance has very essential role inÂ making decision effectively related to the whole process of human resource management. This research purposes to reveal how far the training influences the performance ofÂ employees of BMT Sidogiri in Surabaya and SidoarjoThis research used quantitative approach with saturated sampling method (atechnique of sampling if the entire member of population is used). Consequently it is calledÂ census research. It investigates 34 employees who work as account officer. Data collectedÂ with questionnaires and analyzed with multiple linier regression.The result of this research shows the human resource training variable simultaneouslyÂ and reliably can influence the employeesâ performance based on the result of F test is 65,390Â with significance level is 0,000. The contribution of human resource training is 92.1% with theÂ rest is the other variables. Partially, all human resource variable influences to the employeesâÂ performance according to t test result (the each level of training instructor variable, trainingÂ participants variable, training method, training material, and training facility is less than 0,05).Â Training facility is the dominant variable regards to the employeesâ performance with 0,374Â beta level.